Sledovi pleistocenske poledenitve Stare Galičice, Makedonija = Remmants of Pleistocene glaciation on Stara Galičica Mountain, Macedonia - Uroš Stepišnik; Karel Natek; Manja Žebre; Gregor Fabeković; Valentina Pajk; Simon Koblar; Dunja Ropret; Aljaž Šimon (University of Ljubljana Press (Založba Univerze v Ljubljani), 2012)
The Stara Galičica Mountain was highly reshaped by glacial processes during the Pleistocene.Based on the detailed morphographical mapping of glacial features, the extent ofglaciation was determined as being far larger than described in previous references. The innerpart of the massif was covered with an ice-cap from where outlet glaciers were flowingout. On the basis of morphometrical analysis of glacial features, the altitude of the glacierequilibrium line during the Last Glacial Maximum was established at 1840 m a.s.l.